Oral Bacteriotherapy Reduces the Occurrence of Chronic Fatigue in COVID-19 Patients - Santinelli, Letizia; Laghi, Luca; Innocenti, Giuseppe Pietro; Pinacchio, Claudia; Vassalini, Paolo; Celani, Luigi; Lazzaro, Alessandro; Borrazzo, Cristian; Marazzato, Massimiliano; Tarsitani, Lorenzo; Koukopoulos, Alexia E.; Mastroianni, Claudio M.; et al. (Frontiers in Nutrition, 2022)
Long COVID refers to patients with symptoms as fatigue, “brain fog”, pain, suggesting the chronic involvement of the central nervous system (CNS) in COVID-19. The supplementation with probiotic (OB) would have a positive effect on metabolic homeostasis, negatively im-pacting the occurrence of symptoms related to the CNS after hospital discharge. On a total of 58 patients hospitalized for COVID-19, 24 (41.4%) received OB during hospitalization (OB+) while 34 (58.6%) taken only the standard treatment (OB-). Serum metabolomic profiling of patients has been performed at both hospital acceptance (T0) and discharge (T1). Six months after dis-charge, fatigue perceived by participants was assessed by administrating the Fatigue Assessment Scale. 70.7% of participants reported fatigue while 29.3% were negative for such condition. The OB+ group showed a significantly lower proportion of subjects reporting fatigue than the OB- one (p <0.01). Furthermore, OB+ subjects were characterized by significantly increased con-centrations of serum Arginine, Asparagine, Lactate opposite to lower levels of 3-Hydroxyisobutirate than those not treated with probiotics. Our results strongly suggest that in COVID-19, the administration of probiotics during hospitalization may prevent the development of chronic fatigue by impacting key metabolites involved in the utilization of glucose as well as in energy pathways.